FEATURES OF CHRONIC GASTRO-INTESTINAL DISEASES IN CHILDREN WITH ORTHODONTIC PATHOLOGY - Sirotchenko, T.A.; Kalinichenko, Y.A. (World of Medicine and Biology, 2012)
Orthodontic unremovable apparatus for children with chronic pathology of GIT, associated with Helicobacter pylori, is a substantial negative factor, defiant intensifying of basic disease, by reason of increase of activity of the most microbal causative agent, worsening of hygiene of cavity of mouth and state of fabrics of paradontium of children, that, in turn, can hamper the process of treatment. It requires development and introduction in stomatological practice of complex of medical and preventive measures for the decline of risk of intensifying of diseases of GIT for children on a background treatment an unremovable orthodontic apparatus.